Haji Bawakaraeng: The Resistence of Local Society in South Sulawesi - Mustaqim Pabbajah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
This research aims to explore the existence of Haji Bawakaraeng community tradition in South Sulawesi that is still consistent to depend and to keep their belief, also their resistance in depending their tradition. Besides that, researcher wants to describe the ritual phenomenon in the top of Bawakaraeng mountain.This research is the field research focused on the study about ritual tradition of Haji Bawakaraeng in South Sulawesi. Data collection is done with field observation way by using analysis descriptive method that is to observe natural condition and the social life directly to find out the data about the existence of Haji Bawakaraeng community. Data collection is also done by interviewing the figures and the believers of Haji Bawakaraeng deeply, also the documentation study done to complete the data obtained beforehand. The collected data then will be analyzed by using socio- anthropologic approach and will be explored in a qualitative descriptive way. This research shows that the ritual tradition of Haji Bawakaraeng practiced by the believer of this belief still exists until today, although they face many obstacles. They remain depending their belief strongly practiced since a long time ago by doing adaptation and negotiation of any resistance that they face at present.